FEATURES OF THE INTRODUCTION OF INNOVATIVE TECHNOLOGIES «FORMATION OF PSYCHOLOGICAL READINESS FOR INNOVATIVE ACTIVITY» AND «DEVELOPMENT OF PSYCHOLOGICAL COMPETENCE COMPETITIVENESS PERSONALITIES» USING DIGITAL AND STEM METHODS IN THE PRACTICE OF MODERN EDUCATION - Chudakova, V.P. (Publisher of Kostanay Regional University named after Akhmet Baitursynov, 2024)
The article presents the features of t he introduction of innovation activitye technologies using digital and STEM methods in the practice of modern education. The general design, structure and results of the implementation of two proprietary technologies are revealed: 1) «Technology for the formation of psychological readiness for innovative activity» (V. Chudakova, 2008–2016). 2). «Technology for the formation of psychological competence of individual competitiveness in the conditions of innovative activity» (V. Chudakova, 2016–2024)/
Keywords: innovativeness; innovative activity; formation of psychological readiness for innovative activity; formation of psychological competencies of individual competitiveness; technology